PERAN GURU AGAMA DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL DAN SPIRITUAL PADA ANAK SMP ISLAM DARUSSA’ADAH PONCOKUSUMO - Muhammad Firdausi; Khoirul Asfiyak; Moch Eko Nasrulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Education is the process of maturing and developing in two aspects that are present in humans, namely the biological and psychological aspects. In society the duties and roles of a teacher are truly unlimited, let alone the nature of a teacher. In this case the researchers found the uniqueness found in Darussa'adah Islamic Middle School students because of the very childish behavior of the students. In this factor whether students are able to develop emotional and spiritual intelligence at school, it is necessary to review the educator and what efforts educators do to develop students' emotional and spiritual intelligence. The purpose of this research is to find out what are the efforts of Darussa'adah Islamic Middle School Islamic Religious Education teachers and to know what factors support and hinder the development of emotional and spiritual intelligence. The results of the study explain the efforts of Darussa'adah Islamic Middle School teachers in developing students' emotional and spiritual intelligence. The teacher always advises, motivates teachers to use rote methods to test emotional and spiritual intelligence, and the teacher tells the stories of pious people about patience and gratitude, and gives questions to students. The supporting factors are a beautiful cool environment, complete infrastructure, and totality teachers in educating students. The inhibiting factor is that students have difficulty adapting, and are easily influenced by their peers.